Upaya Perpustakaan dalam Mendukung Pencarian Literasi Informasi Penyandang Disabilitas di Dinas Kearsipan dan Perpustakaan Kabupaten Karanganyar - Nisrina Nida Salma; Imam Mahmudi (Jurnal Gema Pustakawan, 2025)
This study aims to determine the efforts of the Archives and Library Service of Karanganyar Regency in supporting information literacy for people with disabilities. The method used is descriptive qualitative with data collection techniques such as interviews, observation, documentation, and literature review. The results of the study indicate that libraries support information literacy by providing physical and digital accessibility facilities, such as guiding blocks, braille rooms, braille books, and braille computers. In addition, support is also provided through direct assistance by librarians and a process of periodically identifying users' information needs. However, libraries still face obstacles in the form of limited access for people with disabilities to general collections. Therefore, improving the quality of services and expanding the accessibility of collections is essential to encourage independence for people with disabilities in obtaining information. Overall, this study confirms that libraries have a very crucial role in realizing inclusive and equitable access to information services for all levels of society.